Gel polymer electrolyte, method of preparing the same, and use thereof

CN122968136APending Publication Date: 2026-10-23BEIFANG UNIV OF NATITIES +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611436374.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-15
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004](2)游离钾盐的快速流失:传统体系中KCl以游离态存在,受热后迅速气化逸散,无法在材料表面形成持久保护屏障,阻燃效果随时间急剧衰减

Benefits of technology

(1)力学性能全面提升:PDA壳层通过其邻苯二酚/胺基与AWCFA表面羟基及SA/PAM聚合物链形成密集的多重氢键网络,构建连续的有机/无机纳米界面相,显著提升拉伸强度、压缩强度和抗疲劳性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968136A_ABST
    Figure CN122968136A_ABST
Patent Text Reader

Abstract

This invention relates to the field of flame-retardant all-solid-state electrolyte materials, and discloses a gel polymer electrolyte, its preparation method, and its applications. This invention utilizes a PDA shell to react with electrolyte salt metal cations (e.g., K+). + The nanoconfining effect of ) can confine electrolyte salt metal cations (such as K) during combustion. + The PDA is locked in the condensed phase, transforming it into a highly efficient char-forming catalyst. This catalyst synergistically forms a dense "organic-inorganic hybrid carbon-ceramic" flame-retardant barrier with AWCFA, fundamentally shifting the flame-retardant mechanism from traditional gas-phase free radical capture to condensed-phase catalytic char formation. Theoretical calculations reveal the regulatory mechanism of the PDA interface layer on ion transport and interfacial interactions. This invention provides a novel material design scheme for high-safety, long-life all-solid-state energy storage devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of flame-retardant all-solid-state electrolyte materials technology, specifically to a gel polymer electrolyte, its preparation method, and its application. Background Technology

[0002] All-solid-state supercapacitors have broad application prospects in flexible electronics, wearable devices, and smart grids due to their high power density, long cycle life, and good safety. The gel polymer electrolyte, as its core material, directly determines the energy storage efficiency, safety, and service life of the device.

[0003] Existing interpenetrating network gel electrolyte systems face the following core challenges: (1) Single flame retardant mechanism: Existing flame retardant designs mostly rely on the gas-phase free radical capture mechanism of free halogen salts (such as KCl). This "gas-phase fire extinguishing" approach has limited effectiveness in suppressing the intensity of fire spread—that is, the peak heat release rate (HRR). From the perspective of fire safety engineering, HRR is the core parameter that determines the fire hazard level and the time for personnel to escape.

[0004] (2) Rapid loss of free potassium salt: In the traditional system, KCl exists in a free state and is rapidly vaporized and dissipated after being heated. It cannot form a durable protective barrier on the material surface, and the flame retardant effect decays rapidly over time.

[0005] (3) Outdated ion introduction methods: Existing systems generally introduce electrolyte salts by immersing the gel in KCl solution after gel formation. This process is lengthy (usually more than 24 hours), and the KCl concentration is distributed in a gradient. High concentration areas are prone to forming ion clusters, which reduces the effective ion utilization rate.

[0006] (4) Difficulty in achieving multiple properties simultaneously: In pursuing flame retardant properties, mechanical flexibility and electrochemical properties are often sacrificed. Simply adding inorganic flame retardant fillers will block ion transport channels; adding organic flame retardants may interfere with the stability of the electrode / electrolyte interface.

[0007] Polydopamine (PDA) possesses abundant catechol and amino functional groups and excellent carbonization capabilities. However, there are no existing reports on applying PDA coating technology to electrolyte salt particles to construct an embedded ion source and synergistically constructing an organic / inorganic integrated condensed phase flame retardant system with AWCFA. Summary of the Invention

[0008] The purpose of this invention is to overcome the problems existing in the prior art and to provide a gel polymer electrolyte, its preparation method, and its application.

[0009] The core concept of this invention lies in constructing an organic / inorganic nanoparticle synergistic enhancement system, in which polydopamine-coated electrolyte salt organic nanoparticles serve as both an internal ion source and a flame-retardant core unit, and hydroxylated fly ash (AWCFA) inorganic nanoparticles serve as a rigid framework and a flame-retardant template. This system is then embedded within a sodium alginate / polyacrylamide interpenetrating network matrix, and activated via Ca²⁺. + Ionic crosslinking achieves multi-level network synergy of "covalent crosslinking-ionic crosslinking-nano reinforcement".

[0010] To achieve the above objectives, the first aspect of the present invention provides a gel polymer electrolyte, wherein the gel polymer electrolyte comprises a sodium alginate / polyacrylamide interpenetrating network matrix and an organic / inorganic nanoparticle synergistic enhancement system uniformly dispersed in the matrix; The organic / inorganic nanoparticle synergistic enhancement system consists of polydopamine-coated electrolyte salt organic nanoparticles and hydroxylated fly ash inorganic nanoparticles.

[0011] This invention constructs an organic / inorganic integrated condensed phase flame retardant and reinforcing system by synergistically embedding polydopamine-coated electrolyte salt organic nanoparticles and hydroxylated fly ash inorganic nanoparticles into a sodium alginate / polyacrylamide interpenetrating network matrix.

[0012] A second aspect of the present invention provides a method for preparing a gel polymer electrolyte according to the first aspect, wherein the method includes the following steps: (1) Mix sodium alginate solution with an aqueous suspension containing polydopamine-coated electrolyte salt organic nanoparticles, hydroxylated fly ash inorganic nanoparticles and surfactants, and add acrylamide monomer, crosslinking agent and initiator to obtain precursor mixture; (2) After deoxygenating the precursor mixture obtained in step (1), a free radical polymerization reaction is carried out to polymerize and crosslink the acrylamide monomer to form a polyacrylamide network, which physically interpenetrates with the sodium alginate network to obtain a primary interpenetrating network gel. (3) Immerse the primary interpenetrating network gel obtained in step (2) in a solution containing Ca²⁺. + In aqueous solution, Ca² + The polymer diffuses into the gel and coordinates with the guluronic acid units on the sodium alginate chain to form an "egg box" structure, thus completing ionic cross-linking; after removal, it is washed with water to obtain the gel polymer electrolyte.

[0013] A third aspect of the present invention provides a gel polymer electrolyte obtained according to the preparation method described in the second aspect.

[0014] The fourth aspect of the present invention provides the application of the gel polymer electrolyte according to the first or third aspect in the preparation of flame-retardant all-solid-state supercapacitors.

[0015] The fifth aspect of the present invention provides an all-solid-state supercapacitor comprising a gel polymer electrolyte according to the first or third aspect.

[0016] The beneficial technical effects achieved by the present invention through the above technical solution are as follows: (1) Comprehensive improvement of mechanical properties: The PDA shell forms a dense multi-hydrogen bond network with the hydroxyl groups on the surface of AWCFA and the SA / PAM polymer chain through its catechol / amine groups, constructing a continuous organic / inorganic nano-interface phase, which significantly improves tensile strength, compressive strength and fatigue resistance.

[0017] (2) Comprehensive improvement in flame retardancy and thermal stability: The condensed phase catalytic char formation mechanism significantly reduces PHRR; AWCFA-PDA-electrolyte salt metal cations (e.g., K) + The dense carbon layer formed by the synergistic process endows the material with excellent carbon retention at high temperatures.

[0018] (3) Comprehensive improvement in electrochemical performance: Polydopamine-coated electrolyte salt organic nanoparticles serve as an internal ion source, and the electrolyte salt metal cations (e.g., K+) are integrated into the electrolyte salt. + The PDA shell exhibits uniform pre-distribution and is free of ion cluster problems. It is also effective against electrolyte salt metal cations (e.g., K+). + The "capture-release" effect of the device homogenizes the interfacial ion flux, giving the device excellent stability with near-zero decay for more than 30,000 cycles. Attached Figure Description

[0019] Figure 1 This is a schematic diagram illustrating the preparation of PDA@KCl and its synergistic enhancement with AWCFA in a sodium alginate / polyacrylamide interpenetrating network in this invention; wherein, (a) is a schematic diagram of the preparation of gel electrolyte and device assembly process; (b) is a schematic diagram of the formation mechanism of PDA@KCl core-shell particles; (c) is a schematic diagram of the microstructure of multi-level cross-linking and ion transport in the interpenetrating network; and (d) is a schematic diagram of the multiple interactions between multi-level cross-linking and KCl@PDA in the interpenetrating network.

[0020] Figure 2 The graphs show a comparison of the mechanical properties of the gel polymer electrolytes prepared in Example 1, Comparative Example 1, and Comparative Example 2 of this invention; where (a) is the compressive stress-strain curve and (b) is the tensile stress-strain curve.

[0021] Figure 3The graphs show the comparison of HRR, THR, and TSP of the gel polymer electrolytes prepared in Examples 1, 1, and 2 of this invention; where (a) is the curve of heat release rate (HRR) changing with time; (b) is the curve of total heat release (THR) changing with time; and (c) is the curve of total smoke generation (TSP) changing with time.

[0022] Figure 4 The thermogravimetric analysis comparison diagrams of the gel polymer electrolytes prepared in Example 1, Comparative Example 1, and Comparative Example 2 of this invention are shown.

[0023] Figure 5 The figures show a comparison of the electrochemical performance of Examples 1-3 and Comparative Examples 1-3 of the present invention; wherein, (a) is a cyclic voltammetry (CV) curve; (b) is a galvanostatic charge-discharge (GCD) curve; (c) is an electrochemical impedance spectroscopy (EIS) Nyquist plot; and (d) is a rate performance curve.

[0024] Figure 6 This is a long-cycle stability diagram of the supercapacitor assembled in Embodiment 1 of the present invention.

[0025] Figure 7 Particle size distribution diagrams for AWCFA, PDA, and PDA@KCl.

[0026] Figure 8 The following are plots of the results of DFT theoretical calculations (ESP distribution, HOMO-LUMO energy levels, and RDG scatter plots); where (a) is the electrostatic potential (ESP) distribution plot; (b) is the HOMO-LUMO energy level comparison plot; and (c)-(e) are the reduced density gradient (RDG) scatter plots for different systems. Detailed Implementation

[0027] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0028] The decisive innovations of this invention are as follows: (1) Built-in ion source design This invention utilizes polydopamine-coated electrolyte salt nanoparticles as an embedded ion source, pre-encapsulating the electrolyte salt ions and embedding them within the gel precursor, achieving uniform pre-distribution of ions during polymerization and cross-linking. This design fundamentally eliminates the traditional "post-soaking in salt solution" process, significantly shortening the preparation cycle while avoiding ion gradient distribution and ion cluster problems. The "uniform pre-distribution" described in this application refers to spatial uniformity achieved in a heterogeneous system through uniform dispersion of nanoparticles and a sustained-release ion mechanism.

[0029] (2) Paradigm shift in flame retardant mechanism The traditional flame-retardant mechanism of free KCl is as follows: KCl vaporizes upon heating → releases Cl• free radicals → captures H• and OH• in the gas phase → interrupts the combustion chain reaction. Under this mechanism, KCl is rapidly lost, resulting in limited HRR inhibition effect.

[0030] This invention uses the PDA shell to target K + The nano-confinement effect achieves a fundamental shift in the flame-retardant mechanism: the PDA shell stores K during combustion. + Locked in the condensed phase → K + It transforms into a highly efficient char-forming catalyst and crosslinking agent → catalyzes the formation of a highly graphitized carbon layer between PDA and the polymer matrix → tightly binds with the AWCFA nanotemplate → forming a dense "organic-inorganic hybrid carbon-ceramic" condensed phase flame-retardant barrier. This barrier greatly delays the transfer of heat and oxygen, reducing the HRR to an extremely low level, thus inhibiting the intensity of fire spread at its source.

[0031] The first aspect of the present invention provides a gel polymer electrolyte, wherein the gel polymer electrolyte comprises a sodium alginate / polyacrylamide interpenetrating network matrix and an organic / inorganic nanoparticle synergistic enhancement system uniformly dispersed in the matrix; The organic / inorganic nanoparticle synergistic enhancement system consists of polydopamine-coated electrolyte salt organic nanoparticles and hydroxylated fly ash inorganic nanoparticles.

[0032] In this invention, the polydopamine-coated electrolyte salt organic nanoparticles simultaneously function as a built-in ion source and a condensed phase flame-retardant core unit; the gel polymer electrolyte does not require additional soaking in electrolyte salt solutions of any concentration during preparation, and its ionic conductivity is directly provided by the built-in ion source of the polydopamine-coated electrolyte salt organic nanoparticles.

[0033] Polydopamine-coated electrolyte salt organic nanoparticles utilize the nano-confinement effect of the polydopamine shell to release electrolyte salt metal cations (e.g., K+) during combustion. + It is locked in the condensed phase, transforming it from a traditional free potassium salt gas-phase free radical scavenger into a condensed phase char-forming catalyst, thereby achieving a fundamental shift in the flame retardant mechanism from gas-phase inhibition to a condensed phase catalytic char-forming barrier.

[0034] During combustion, hydroxylated fly ash inorganic nanoparticles act as rigid nanotemplates, reacting with the carbonization products of polydopamine and electrolyte salt metal cations (such as K+). + The highly graphitized carbon layers generated by catalysis jointly construct a dense "organic-inorganic hybrid carbon-ceramic" condensed phase flame-retardant barrier.

[0035] Furthermore, on the surface, the electrolyte salt appears to be encapsulated within a polydopamine shell, forming a solid core confined within nanoscale zones, rather than dissolving directly in the solvent in ionic form. However, in practical applications, the polydopamine shell is not airtight—water molecules can penetrate the shell and enter the core to dissolve the electrolyte salt. The electrolyte salt's ions (e.g., K+)... + and Cl - It can also be slowly released into the gel network. The polydopamine shell is resistant to electrolyte salt metal cations (e.g., K+). + It exerts a "capture-slow release" effect, which is essentially a controlled release mechanism rather than a permanent closure.

[0036] In some embodiments of the present invention, the sodium alginate chains in the sodium alginate / polyacrylamide interpenetrating network matrix are mediated by Ca²⁺. + Ionic cross-linking occurs to form an "egg box" structure.

[0037] In some embodiments of the present invention, the network formed by the ionic crosslinking, together with the organic / inorganic nanoparticle synergistic reinforcement system, constitutes a multi-level synergistic network of "covalent crosslinking-ionic crosslinking-nano reinforcement". Covalent crosslinking refers to the chemical bond crosslinking in the polyacrylamide (PAM) network formed by a chemical crosslinking agent (e.g., MBA).

[0038] In some embodiments of the present invention, the electrolyte salt is selected from at least one of potassium chloride, lithium chloride, sodium sulfate, zinc chloride and sodium perchlorate, preferably potassium chloride.

[0039] In some embodiments of the present invention, the electrolyte salt is encapsulated inside the polydopamine shell in a saturated or near-saturated state.

[0040] In some embodiments of the present invention, the mass ratio of the organic / inorganic nanoparticle synergistic reinforcement system to the sodium alginate / polyacrylamide interpenetrating network matrix is ​​0.4-1.5:1.0-2.0, preferably 0.6-0.8:1.3, and more preferably 0.7:1.3; In some embodiments of the present invention, the mass ratio of the polydopamine-coated electrolyte salt organic nanoparticles to the hydroxylated fly ash inorganic nanoparticles is 0.1-0.5:0.3-1.0, preferably 0.1-0.3:0.5, and more preferably 0.2:0.5.

[0041] A second aspect of the present invention provides a method for preparing a gel polymer electrolyte according to the first aspect, wherein the method includes the following steps: (1) Mix sodium alginate solution with an aqueous suspension containing polydopamine-coated electrolyte salt organic nanoparticles, hydroxylated fly ash inorganic nanoparticles and surfactants, and add acrylamide monomer, crosslinking agent and initiator to obtain precursor mixture; (2) After deoxygenating the precursor mixture obtained in step (1), a free radical polymerization reaction is carried out to polymerize and crosslink the acrylamide monomer to form a polyacrylamide network, which physically interpenetrates with the sodium alginate network to obtain a primary interpenetrating network gel. (3) Immerse the primary interpenetrating network gel obtained in step (2) in a solution containing Ca²⁺. + In aqueous solution, Ca² + The polymer diffuses into the gel and coordinates with the guluronic acid units on the sodium alginate chain to form an "egg box" structure, thus completing ionic cross-linking; after removal, it is washed with water to obtain the gel polymer electrolyte.

[0042] In this invention, the preparation process does not require additional soaking in electrolyte salt solutions of any concentration. The ionic conductivity of the electrolyte is directly provided by pre-prepared polydopamine-coated electrolyte salt organic nanoparticles embedded in a gel network.

[0043] In some embodiments of the present invention, the preparation method of the polydopamine-coated electrolyte salt organic nanoparticles includes: reacting electrolyte salt nanoparticles and dopamine hydrochloride under alkaline and aerobic conditions, so that dopamine self-polymerizes in situ on the surface of electrolyte salt nanoparticles to form a polydopamine coating layer, thereby obtaining polydopamine-coated electrolyte salt organic nanoparticles.

[0044] In some embodiments of the present invention, the mass ratio of dopamine hydrochloride to electrolyte salt nanopowder is 1:5-10, preferably 1:5.

[0045] In some embodiments of the present invention, the pH of the alkaline conditions is 8-9, preferably 8.5.

[0046] In some embodiments of the present invention, the reaction is carried out under continuous stirring.

[0047] In some embodiments of the present invention, the reaction temperature is 15-30°C, preferably room temperature.

[0048] In some embodiments of the present invention, the reaction time is 6-10 hours, preferably 8 hours.

[0049] In some embodiments of the present invention, the mass fractions of each component in step (1) are: sodium alginate 0.5-1.0 parts, polydopamine-coated electrolyte salt organic nanoparticles 0.1-0.5 parts, hydroxylated fly ash inorganic nanoparticles 0.3-1.0 parts, surfactant 0.02-0.08 parts, and acrylamide monomer 0.5-1.0 parts.

[0050] In some embodiments of the present invention, the mass fractions of each component in step (1) are: 0.7 parts sodium alginate, 0.1-0.3 parts polydopamine-coated electrolyte salt organic nanoparticles, 0.5 parts hydroxylated fly ash inorganic nanoparticles, 0.04 parts surfactant, and 0.6 parts acrylamide monomer.

[0051] In some embodiments of the present invention, the amount of the crosslinking agent is 0.3-1.0% of the mass of the acrylamide monomer, preferably 0.5%.

[0052] In some embodiments of the present invention, the amount of the initiator is 0.5-2.0% of the mass of the acrylamide monomer, preferably 1%.

[0053] In some embodiments of the present invention, the crosslinking agent is selected from at least one of N,N'-methylenebisacrylamide, N,N'-vinylbisacrylamide and ethylene glycol dimethacrylate, preferably N,N'-methylenebisacrylamide.

[0054] In some embodiments of the present invention, the initiator is at least one selected from ammonium persulfate, potassium persulfate and azobisisobutyramidine hydrochloride, preferably ammonium persulfate.

[0055] In some embodiments of the present invention, the surfactant is selected from at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and polyethylene glycol p-tert-octylphenyl ether (Triton X-100), preferably sodium dodecyl sulfate.

[0056] In some embodiments of the present invention, the temperature of the free radical polymerization reaction in step (2) is 55-65°C, preferably 60°C.

[0057] In some embodiments of the present invention, the free radical polymerization reaction in step (3) takes 6-8 hours, preferably 7 hours.

[0058] In some embodiments of the present invention, step (3) contains Ca² + The concentration of the aqueous solution is 0.2-0.5M, preferably 0.3M.

[0059] In some embodiments of the present invention, the soaking time in step (3) is 6-12 hours, preferably 8 hours.

[0060] According to a particularly preferred embodiment of the present invention, a method for preparing a gel polymer electrolyte, wherein the method comprises the following steps: (1) Preparation of PDA@KCl organic nanoparticles: KCl nanoparticles were dispersed in Tris buffer, and dopamine hydrochloride was added. The mixture was stirred and reacted under alkaline and aerobic conditions to allow dopamine to self-polymerize in situ on the KCl surface to form a polydopamine coating layer. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain PDA@KCl organic nanoparticles. (2) Preparation of precursor mixture: Under ice bath conditions, sodium alginate is dissolved in the first part of deionized water to form sodium alginate solution; AWCFA inorganic nanoparticles, PDA@KCl organic nanoparticles obtained in step (1) and surfactant are added to the second part of deionized water and ultrasonically dispersed to form a uniform organic / inorganic nanoparticle suspension; the obtained suspension is mixed evenly with the obtained sodium alginate solution, and then acrylamide monomer, crosslinking agent and initiator are added and stirred until completely dissolved to obtain precursor mixture; (3) In-situ polymerization to form an interpenetrating network: After passing an inert gas into the precursor mixture obtained in step (2) to remove oxygen, the mixture is heated to carry out a free radical polymerization reaction, so that the acrylamide is polymerized and crosslinked to form a polyacrylamide network, which physically interpenetrates with the sodium alginate network to obtain a primary interpenetrating network gel. (4) Ca² + Ionic crosslinking: The primary gel obtained in step (3) is immersed in an aqueous solution of CaCl2 to allow Ca²⁺ to crosslink with the ion. + It diffuses into the gel and coordinates with the guluronic acid units on the sodium alginate chain to form an "egg box" structure, thus completing ionic cross-linking; (5) Obtain the target electrolyte: Take out the gel after step (4) and rinse the surface with deionized water to obtain the organic / inorganic nanoparticle synergistic reinforcement interpenetrating network gel electrolyte based on condensed phase flame retardancy.

[0061] A third aspect of the present invention provides a gel polymer electrolyte obtained according to the preparation method described in the second aspect.

[0062] The fourth aspect of the present invention provides the application of the gel polymer electrolyte according to the first or third aspect in the preparation of flame-retardant all-solid-state supercapacitors.

[0063] The fifth aspect of the present invention provides an all-solid-state supercapacitor comprising a gel polymer electrolyte according to the first or third aspect.

[0064] Theoretical calculations (density functional theory, DFT) show that extensive weak interactions (confirmed by RDG analysis) formed between the polydopamine-coated electrolyte salt organic nanoparticles, hydroxylated fly ash inorganic nanoparticles, and the interpenetrating network matrix, optimizing the interfacial ion transport environment. Electrostatic potential (ESP) analysis shows that the PDA shell surface is rich in negative potential sites, which is beneficial for K... + Uniform adsorption and orderly transport; HOMO-LUMO band gap analysis shows that the introduction of PDA optimizes the electronic structure of the system and promotes ion migration.

[0065] The present invention will be described in detail below through embodiments.

[0066] Unless otherwise specified in the following examples and comparative examples, all conditions were performed under standard conditions or conditions recommended by the manufacturer. Reagents or instruments used, unless otherwise specified, are all commercially available products.

[0067] Example 1 This example illustrates the preparation of gel polymer electrolytes.

[0068] (1) 1.0 g KCl was ultrasonically dispersed in 100 mL Tris-HCl buffer (10 mM, pH 8.5); 0.2 g dopamine hydrochloride was added and the mixture was stirred continuously at room temperature for 8 h to allow dopamine to self-polymerize in situ on the KCl surface to form a polydopamine coating layer; after the reaction was completed, the precipitate was collected by centrifugation at 10000 rpm for 10 min, washed three times with ethanol and deionized water respectively, and dried at 60 °C for 24 h to obtain PDA@KCl organic nanoparticles.

[0069] (2) Under ice bath conditions, 0.7 g of sodium alginate was dissolved in 15 mL of deionized water and stirred until completely dissolved to form a transparent and viscous solution, namely sodium alginate solution; 0.5 g of AWCFA inorganic nanoparticles, 0.2 g of PDA@KCl organic nanoparticles and 0.04 g of sodium dodecyl sulfate were added to 5 mL of deionized water and ultrasonically dispersed in an ice bath for 30 min to form a uniform organic / inorganic nanoparticle suspension; the obtained suspension was poured into sodium alginate solution and stirred evenly, and then 0.6 g of acrylamide monomer, 0.003 g of crosslinking agent N,N'-methylenebisacrylamide (0.5% of monomer mass) and 0.006 g of initiator ammonium persulfate (1% of monomer mass) were added and stirred until completely dissolved to obtain precursor mixture.

[0070] (3) Nitrogen gas was introduced into the precursor mixture for 30 min to remove oxygen. After sealing, it was placed in an oven at 60°C for in-situ polymerization for 7 h to obtain a primary interpenetrating network gel.

[0071] (4) The primary interpenetrating network gel was immersed in 100 mL of 0.3 M CaCl2 aqueous solution for 8 h to allow Ca²⁺ to settle. + It diffuses into the gel and coordinates with the guluronic acid units on the sodium alginate chain to form an "egg box" structure, thus completing the ionic cross-linking.

[0072] (5) Remove the gel and rinse the surface with deionized water to obtain the organic / inorganic nanoparticle synergistically enhanced interpenetrating network gel polymer electrolyte based on condensed phase flame retardancy.

[0073] Example 2 The gel polymer electrolyte was prepared according to the method of Example 1, except that the amount of PDA@KCl organic nanoparticles added in step (2) was 0.1g.

[0074] Example 3 The gel polymer electrolyte was prepared according to the method of Example 1, except that the amount of PDA@KCl organic nanoparticles added in step (2) was 0.3g.

[0075] Comparative Example 1 The gel polymer electrolyte was prepared according to the method of Example 1, except that PDA@KCl organic nanoparticles were not added in step (2).

[0076] Comparative Example 2 The gel polymer electrolyte was prepared according to the method of Example 1, except that in step (2), the PDA@KCl organic nanoparticles were replaced with an equal mass of pure polydopamine nanoparticles.

[0077] Comparative Example 3 The gel polymer electrolyte was prepared according to the method of Comparative Example 1, except that after step (3) was completed, the resulting gel was soaked in 100 mL of deionized water (concentration of about 0.022 M) containing 0.167 g KCl for 24 h, so that KCl could be absorbed into the electrolyte. + and Cl - Ion equilibrium is achieved by diffusion into the gel network. After removal, the surface is quickly rinsed with deionized water to obtain the final product.

[0078] Test Example 1 Figure 7The aqueous hydrodynamic particle size distribution of three nanoparticles—AWCFA, PDA, and PDA@KCl—is shown in the diagrams (obtained by dynamic light scattering (DLS)). All three curves exhibit a single, sharp, symmetrical peak without multi-peak splitting or size tailing, indicating excellent dispersion stability and particle size uniformity in the aqueous phase, allowing for uniform implantation into the gel matrix. Furthermore, the average particle size shows a pattern of pure PDA > AWCFA > PDA@KCl, and the PDA@KCl curve lacks the characteristic peak corresponding to free pure PDA, confirming the successful preparation of the PDA@KCl core-shell structure. This demonstrates high efficiency and few byproducts in the heterogeneous nucleation and encapsulation of dopamine using KCl as a template. This microstructural feature facilitates the construction of a multi-level hydrogen bond network and enhances the utilization of KCl. + The nano-confined flame-retardant effect provides a structural basis for achieving uniform and slow-release ion transport, supporting the synergistic improvement of mechanical, flame-retardant and electrochemical properties.

[0079] Test Example 2: Mechanical Property Test Mechanical property tests were conducted on a UTM4304 electronic universal testing machine from Shenzhen Sansi Zongheng Technology Co., Ltd. The compression test used a 10mm × 30mm sample, and the tensile test used a 30mm × 10mm × 4mm sample. The loading rate for both tests was 5mm•min. - ¹.

[0080] Test results are as follows Figure 2 As shown. The gel polymer electrolyte prepared in Example 1 has a compressive strength of 250 kPa at a compressive strain of 60% and a tensile strength of 6 kPa at an elongation at break of 50%, both of which are significantly better than those of Comparative Example 1 and Comparative Example 2.

[0081] Example 1 shows a significant improvement in mechanical properties due to its unique multi-level synergistic network structure of "covalent crosslinking-ionic crosslinking-nano-reinforcement": the polydopamine shell surface of PDA@KCl nanoparticles is rich in catechol and amino functional groups. On the one hand, it forms dense hydrogen bonds with the active hydroxyl groups on the AWCFA surface, constructing a robust organic / inorganic interface phase; on the other hand, it forms multiple hydrogen bonds with the carboxyl groups on the sodium alginate chain and the amide groups on the polyacrylamide chain, making the PDA@KCl particles physical crosslinking nodes between polymer networks. When the gel is subjected to stress, the covalently crosslinked polyacrylamide network maintains the integrity of the overall structure, Ca² +- The sodium alginate "egg box" ionic cross-linked structure dissipates energy through reversible dissociation and recombination. The rigid AWCFA nanoparticles act as a stress dispersion medium to avoid localized stress concentration. The synergistic effect of these three elements results in significantly better compressive and tensile strengths than Comparative Example 1 (only AWCFA, lacking PDA interfacial bridging and ionic cross-linking network) and Comparative Example 2 (PDA and AWCFA are merely physically mixed, lacking the strong interfacial coupling and K-type cross-linking provided by the core-shell structure). + (Nano confinement effect).

[0082] Test Example 3: Flame Retardancy and Thermal Stability Test The thermal stability of the gel polymer electrolyte was evaluated under a nitrogen atmosphere using a Waters China Q50 thermogravimetric analyzer (TGA). The test temperature range was 30 to 600 °C, with a heating rate of 20 °C / min. -1 Its flame-retardant properties were further analyzed using a dual-cone calorimeter manufactured by FireTesting Technology, UK.

[0083] like Figure 3 As shown, the peak heat release rate (HRR) of the gel polymer electrolyte prepared in Example 1 is 26.2 kW•m. - ², Total heat release (THR) is 8.1 MJ•m - ², Total Smoke Output (TSP) is 0.6 m²•kg - ¹, all three indicators were significantly lower than those of Comparative Example 1 and Comparative Example 2; such as Figure 4 As shown, the residual carbon rate of the gel polymer electrolyte prepared in Example 1 at 600℃ is as high as 91.6%, which is significantly higher than that of the two control groups.

[0084] The gel polymer electrolyte prepared in this invention exhibits superior flame retardancy and thermal stability, stemming from the synergistic flame retardant mechanism transformation achieved through the PDA@KCl core-shell structure and AWCFA. During combustion, the polydopamine shell of PDA@KCl, through its nano-confinement effect, confines K+... + Firmly locked in the condensed phase, preventing K + Loss due to heat vaporization; confined K + It transforms into a highly efficient char-forming catalyst, catalyzing the cross-linking and cyclization of PDA and polymer matrix pyrolysis products to form a dense carbon layer with a high degree of graphitization. AWCFA (hydroxylated fly ash) serves as a rigid nanotemplate embedded in this carbon layer, and the three synergistically construct a dense "organic-inorganic hybrid carbon-ceramic" condensed-phase flame-retardant barrier. This barrier significantly delays the transfer of heat, oxygen, and combustible volatiles, resulting in a substantial reduction in HRR and THR, while simultaneously inhibiting smoke generation (significantly reducing TSP), and endowing the material with extremely high char retention capacity at high temperatures. In contrast, Comparative Example 1 (without K) +Catalytic charring relies solely on the physical barrier of AWCFA and its own carbonization, resulting in limited flame retardant effects; while pure PDA in Comparative Example 2 can carbonize itself, K... + Not confined by the PDA shell, it cannot play a catalytic role in carbonization. The carbon layer has a low degree of graphitization and insufficient density. Therefore, its flame retardancy and thermal stability are significantly inferior to those of Example 2.

[0085] Test Example 3: Electrochemical Performance Commercial activated carbon electrodes (2cm × 2cm) were used as the positive and negative electrodes. A gel polymer electrolyte was cut into pieces slightly larger than the electrodes (2.2cm × 2.2cm) and sandwiched between the two activated carbon electrodes, with the active material side of the electrode facing the electrolyte. A pressure of 0.5MPa was applied and held for 30 seconds to ensure tight contact between the electrode and electrolyte interfaces and to remove any residual air bubbles between the layers. Finally, the electrodes were sealed in a plastic bag or aluminum-plastic film to assemble a symmetrical all-solid-state supercapacitor.

[0086] This test case systematically evaluates the electrochemical performance of an all-solid-state supercapacitor using a combination of electrochemical characterization techniques. All tests were performed on a CHI 760E electrochemical workstation.

[0087] Cyclic voltammetry (CV) tests were performed within a voltage window of 0.6–1.4 V, with a scan rate set to 5–100 mV•s. - ¹. The operating voltage range for constant current charge-discharge testing (GCD) is 0.6–1.4 V, and the current density range is 3–7 mA·cm². - ². Electrochemical impedance spectroscopy (EIS) was performed at frequencies from 0.1 Hz to 100 kHz with an applied AC perturbation signal of 5 mV amplitude. Furthermore, a LAND CT2001A battery testing system was used to measure the electrochemical impedance spectroscopy (EIS) over a voltage range of 0–0.8 V with an applied AC perturbation signal of 5 mA•cm⁻¹. - Under a constant current density of ², long-term stability tests of constant current charge-discharge were conducted. The results are as follows: Figure 5-6 As shown in Table 1.

[0088] Table 1

[0089] like Figure 5 As shown in (a), the CV curve of Example 1 exhibits an approximately rectangular symmetrical feature at all scan rates, indicating ideal capacitive behavior and a fast electrochemical response. In contrast, the integrated areas of the CV curves of Comparative Examples 1 and 2 are significantly reduced and deviate from a rectangular shape, reflecting ion depletion and increased polarization due to the lack of an internal ion source. Although the CV curve of Comparative Example 3 has a certain area, it shows slight distortion in the high-potential region, corresponding to free K+. + Uneven adsorption-desorption on the electrode surface.

[0090] like Figure 5 As shown in (b), the GCD curve of Example 1 exhibits a highly symmetrical triangle, with the longest charge-discharge time and a coulombic efficiency approaching 100%. At the same current density, the charge-discharge times of Examples 2 and 3 decrease sequentially with decreasing PDA@KCl dosage, confirming that the built-in ion source of PDA@KCl is the core of ion supply. The GCD curve of Comparative Example 3 shows a significant IR drop (voltage spike) in the discharge initiation phase, corresponding to a higher interface impedance, which is due to free KCl. + Typical characteristics of uneven ion aggregation at the system interface.

[0091] like Figure 5 As shown in (c), in the EIS Nyquist plot, Example 1 has the smallest semicircle diameter in the high-frequency region and the largest straight line slope in the low-frequency region, indicating that it has the lowest charge transfer impedance and the most ideal ion diffusion behavior. In Comparative Examples 1 and 2, the semicircle diameter is significantly increased, indicating that ion scarcity leads to difficulties in interfacial charge transfer. In Comparative Example 3, the straight line slope in the low-frequency region deviates from the ideal value, indicating that free K+... + The system exhibits significant diffusion limitations.

[0092] like Figure 5 (d) and Table 1 show the ionic conductivity of Example 1 (76.06 mS·cm). - ¹) and areal capacitance (711 mF·cm) - ², 3 mA·cm - ²) All were significantly superior to Examples 2, 3, and Comparative Examples 1-3. Specifically: the conductivity of Example 2 (PDA@KCl 0.1g) was 54.43 mS·cm. - ¹, The areal capacitance is 552 mF·cm - ², lower than Example 1 due to insufficient total ion source; the conductivity of Example 3 (PDA@KCl 0.3g) was 68.06 mS·cm. - ¹, The areal capacitance is 671.25 mF·cm. - ², the performance improved but was slightly lower than in Example 1, indicating that excessively high nanofiller content may slightly impede ion channels or induce local aggregation; the conductivity of Comparative Example 1 (no PDA@KCl, no KCl immersion) was only 40.52 mS·cm. - ¹, the areal capacitance is only 460 mF·cm - ², verifying the absolute necessity of the "built-in ion source"; the conductivity and areal capacitance of Comparative Example 2 (pure PDA replacing PDA@KCl) are close to those of Comparative Example 1, proving that PDA alone without a coated electrolyte salt core cannot provide ion conduction; the conductivity of Comparative Example 3 (immersion in free KCl) is 63.08 mS·cm. -¹, The areal capacitance is 620.63 mF·cm. - ², although significantly higher than Comparative Examples 1-2, it is still lower than K in Examples 1-3. + As they migrate freely in a free state, they accumulate unevenly at the electrode / electrolyte interface during charging and discharging, leading to increased interfacial impedance and decreased effective ion utilization.

[0093] like Figure 6 As shown, the supercapacitor assembled in Example 1 operates at 5 mA·cm⁻¹. - ² After cycling over 30,000 times at a constant current density, the capacity retention remained at 100%, with no signs of degradation. This exceptional long-term cycling stability is attributed to the PDA shell's K... + Nanoscale confinement and "capture-and-release" effect—PDA shell will contain K + The uniform release to the interface avoids free K + Interface degradation and capacity decay in the system are caused by uneven ion aggregation and dissipation. Figure 6 The GCD curves in the system completely overlap at different stages of the cycle, further confirming the system's excellent electrochemical reversibility and interfacial stability. The inventors also performed the following theoretical calculations, such as Figure 8 As shown: Electrostatic potential (ESP) analysis is used to characterize the charge distribution on the surface of molecules or materials. Calculations show that the PDA shell surface is rich in negatively charged sites, primarily originating from oxygen atoms in the catechol group and nitrogen atoms in the amine group. This conclusion explains the "capture-and-release" effect and excellent electrochemical performance of this invention at the molecular level: K + Ordered adsorption: The negatively charged PDA shell attracts positively charged K+ through Coulomb forces. + Adsorbed on the surface, making K + The PDA layers are arranged in an ordered manner, rather than being randomly distributed in a free state. This lowers the migration barrier: K + Ion transport occurs via a "jumping" motion along negatively charged sites on the PDA surface, guided by the electrostatic potential gradient of the PDA surface, effectively reducing the activation energy of ion transport. Homogenized ion flux: Each PDA@KCl particle acts as a negatively charged "ion transfer station," attracting K+ ions. + The ions are evenly distributed around the electrode, which avoids the uneven aggregation of ions on the electrode surface in the free KCl system and the resulting increase in interfacial impedance.

[0094] The band gaps between the HOMO (highest occupied molecular orbital) and LUMO (lowest unoccupied molecular orbital) reflect the chemical reactivity and electron transport capability of the system. Calculations show that the introduction of PDA optimizes the electronic structure of the system and reduces the HOMO-LUMO band gap. This conclusion explains the promoting effect of PDA on ion migration at the molecular level: enhanced interfacial electronic coupling; a smaller band gap means that the PDA shell and K... + The electron clouds between polymer chains are more likely to overlap and interact, which facilitates rapid ion exchange at the interface. This promotes ion migration: the reduced bandgap makes the system more responsive to an applied electric field, and the "jumping" migration of ions is smoother, macroscopically manifested as higher ionic conductivity. It also stabilizes the interface structure: the optimized electronic structure allows for better interaction between PDA and K... + The binding strength is moderate—strong enough to achieve nanoscale confinement and "trapping" functionality, but not so strong as to over-confine K. + And this hinders its "slow release" and transmission.

[0095] RDG (reduced density gradient) analysis was used to visualize the region and strength of non-covalent interactions (such as hydrogen bonds, van der Waals forces, and steric hindrance) in the system. Calculations showed that PDA@KCl formed a broad and dense network of weak interactions with AWCFA and sodium alginate / polyacrylamide chains. This conclusion explains three macroscopic properties at the molecular level: (1) Mechanical enhancement: The dense hydrogen bond network is the molecular basis for the PDA shell to act as an interfacial bridge and construct an "organic / inorganic nano-interfacial phase". (2) Flame retardant synergy: The weak interaction ensures the synergistic effect of PDA carbonization products and K + The catalytic carbon layer and the rigid template of AWCFA remain tightly coupled at high temperatures, avoiding phase separation, which is a prerequisite for the formation of a dense "carbon-ceramic" barrier. (3) Structural stability: Extensive interactions firmly anchor PDA@KCl particles in the gel network, preventing them from migrating or falling off during long-term cycling and stress deformation.

[0096] The above results demonstrate that this invention, by introducing PDA@KCl organic nanoparticles as a built-in ion source and condensed-phase flame-retardant core unit, and synergistically constructing an organic / inorganic integrated reinforcement system with AWCFA inorganic nanoparticles, simultaneously achieves comprehensive breakthroughs in mechanical, flame-retardant and thermal stability, and electrochemical performance without any external KCl soaking. The core-shell structure of PDA@KCl is the decisive factor in achieving this breakthrough.

[0097] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A gel polymer electrolyte, characterized in that, The gel polymer electrolyte comprises a sodium alginate / polyacrylamide interpenetrating network matrix and an organic / inorganic nanoparticle synergistic enhancement system uniformly dispersed in the matrix. The organic / inorganic nanoparticle synergistic enhancement system consists of polydopamine-coated electrolyte salt organic nanoparticles and hydroxylated fly ash inorganic nanoparticles.

2. The gel polymer electrolyte according to claim 1, wherein, The sodium alginate chains in the sodium alginate / polyacrylamide interpenetrating network matrix are mediated by Ca²⁺ + Ionic cross-linking is carried out to form an "egg box" structure; Preferably, the network formed by the ionic crosslinking and the organic / inorganic nanoparticle synergistic reinforcement system together constitute a multi-level synergistic network of "covalent crosslinking-ionic crosslinking-nano reinforcement".

3. The gel polymer electrolyte according to claim 1 or 2, wherein, The electrolyte salt is selected from at least one of potassium chloride, lithium chloride, sodium sulfate, zinc chloride and sodium perchlorate, preferably potassium chloride; Preferably, the electrolyte salt is encapsulated inside the polydopamine shell in a saturated or near-saturated state.

4. The gel polymer electrolyte according to any one of claims 1-3, wherein, The mass ratio of the organic / inorganic nanoparticle synergistic reinforcement system to the sodium alginate / polyacrylamide interpenetrating network matrix is ​​0.4-1.5:1.0-2.0, preferably 0.6-0.8:1.3, and more preferably 0.7:1.3; Preferably, the mass ratio of the polydopamine-coated electrolyte salt organic nanoparticles to the hydroxylated fly ash inorganic nanoparticles is 0.1-0.5:0.3-1.0, more preferably 0.1-0.3:0.5, and even more preferably 0.2:0.

5.

5. A method for preparing a gel polymer electrolyte according to any one of claims 1-4, characterized in that, The method includes the following steps: (1) Mix sodium alginate solution with an aqueous suspension containing polydopamine-coated electrolyte salt organic nanoparticles, hydroxylated fly ash inorganic nanoparticles and surfactants, and add acrylamide monomer, crosslinking agent and initiator to obtain precursor mixture; (2) After deoxygenating the precursor mixture obtained in step (1), a free radical polymerization reaction is carried out to polymerize and crosslink the acrylamide monomer to form a polyacrylamide network, which physically interpenetrates with the sodium alginate network to obtain a primary interpenetrating network gel. (3) Immerse the primary interpenetrating network gel obtained in step (2) in a solution containing Ca²⁺. + In aqueous solution, Ca² + The polymer diffuses into the gel and coordinates with the guluronic acid units on the sodium alginate chain to form an "egg box" structure, thus completing ionic cross-linking; after removal, it is washed with water to obtain the gel polymer electrolyte.

6. The method according to claim 5, wherein, The preparation method of the polydopamine-coated electrolyte salt organic nanoparticles includes: reacting electrolyte salt nanoparticles and dopamine hydrochloride under alkaline and aerobic conditions, so that dopamine self-polymerizes in situ on the surface of electrolyte salt nanoparticles to form a polydopamine coating layer, thereby obtaining polydopamine-coated electrolyte salt organic nanoparticles. Preferably, the mass ratio of dopamine hydrochloride to electrolyte salt nanopowder is 1:5-10, more preferably 1:5; Preferably, the pH of the alkaline condition is 8-9, and more preferably 8.5; Preferably, the reaction is carried out under continuous stirring; Preferably, the reaction temperature is 15-30°C, and more preferably room temperature; Preferably, the reaction time is 6-10 hours, and more preferably 8 hours.

7. The method according to claim 5 or 6, wherein, The mass fractions of each component in step (1) are: sodium alginate 0.5-1.0 parts, polydopamine-coated electrolyte salt organic nanoparticles 0.1-0.5 parts, hydroxylated fly ash inorganic nanoparticles 0.3-1.0 parts, surfactant 0.02-0.08 parts, and acrylamide monomer 0.5-1.0 parts. Preferably, the mass fractions of each component in step (1) are: 0.7 parts sodium alginate, 0.1-0.3 parts polydopamine-coated electrolyte salt organic nanoparticles, 0.5 parts hydroxylated fly ash inorganic nanoparticles, 0.04 parts surfactant, and 0.6 parts acrylamide monomer. Preferably, the amount of the crosslinking agent is 0.3-1.0% of the mass of the acrylamide monomer, and more preferably 0.5%. Preferably, the amount of the initiator is 0.5-2.0% of the mass of the acrylamide monomer, more preferably 1%; Preferably, the crosslinking agent is selected from at least one of N,N'-methylenebisacrylamide, N,N'-vinylbisacrylamide and ethylene glycol dimethacrylate, and is more preferably N,N'-methylenebisacrylamide; Preferably, the initiator is selected from at least one of ammonium persulfate, potassium persulfate, and azobisisobutyramidine hydrochloride, and is preferably ammonium persulfate; Preferably, the surfactant is selected from at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and polyethylene glycol p-tert-octylphenyl ether, and is preferably sodium dodecyl sulfate; Preferably, the temperature of the free radical polymerization reaction in step (2) is 55-65℃, and more preferably 60℃; Preferably, the free radical polymerization reaction in step (3) takes 6-8 hours, more preferably 7 hours; Preferably, step (3) contains Ca² + The concentration of the aqueous solution is 0.2-0.5M, preferably 0.3M; Preferably, the soaking time in step (3) is 6-12 hours, preferably 8 hours.

8. The gel polymer electrolyte obtained by the preparation method according to any one of claims 5-7.

9. The application of the gel polymer electrolyte according to any one of claims 1-4 and 8 in the preparation of flame-retardant all-solid-state supercapacitors.

10. An all-solid-state supercapacitor comprising a gel polymer electrolyte according to any one of claims 1-4 and 8.